2020
DOI: 10.1177/1753425920930074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of berberine on LPS-induced expression of NF-κB/MAPK signalling pathway and related inflammatory cytokines in porcine intestinal epithelial cells

Abstract: Berberine is an alkaloid extracted from medicinal plants such as Coptis chinensis and Phellodendron chinense. It possesses anti-inflammatory, anti-tumour and anti-oxidation properties, and regulates Glc and lipid metabolism. This study explored the mechanisms of the protective effects of berberine on barrier function and inflammatory damage in porcine intestinal epithelial cells (IPEC-J2) induced by LPS. We first evaluated the effects of berberine and LPS on cell viability. IPEC-J2 cells were treated with 5 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Our results indicated that the A. rugosa extract exerts anti-inflammatory effects by decreasing NO production in LPS-induced RAW 264.7 cells. In other words, NF-κB, a transcription factor, is activated by LPS in the inflammatory response and can regulate the expression of inflammatory genes such as IL-1β, TNF-α, and iNOS [42]. The gastro-protective effects of A. rugosa were determined based on the reversal of mucosal damage, which was measured by ulceration index and analysis of histological changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that the A. rugosa extract exerts anti-inflammatory effects by decreasing NO production in LPS-induced RAW 264.7 cells. In other words, NF-κB, a transcription factor, is activated by LPS in the inflammatory response and can regulate the expression of inflammatory genes such as IL-1β, TNF-α, and iNOS [42]. The gastro-protective effects of A. rugosa were determined based on the reversal of mucosal damage, which was measured by ulceration index and analysis of histological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that the A. rugosa extract exerts anti-inflammatory effects by decreasing NO production in LPS-induced RAW 264.7 cells. In other words, NF-κB, a transcription factor, is activated by LPS in the inflammatory response and can regulate the expression of inflammatory genes such as IL-1β, TNF-α, and iNOS [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the regulatory role of NF-κB in inflammation has been confirmed. As key markers of the NF-κB pathway, p-IκBα and p-P65 are usually used to evaluate the activation of the NF-κB pathway (Zhu et al, 2020). Therefore, the expression of YAP, p-IκBα, and p-P65 in RAW264.7 cells was detected to investigate the effect of Ti ions on Hippo/YAP and NF-κB pathways.…”
Section: Increased Secretion Of Pro-inflammatory Cytokines In Macromentioning
confidence: 99%
“…1 Over the past 20 years, its multiple pharmacological activities have been discovered and elucidated, including antiinflammatory, antitumor, hypoglycemic, hypolipidemic, antivirus, etc, [2][3][4][5][6][7][8][9][10][11] suggesting a typical multitargetdirected mechanism of BBR. A couple of classical cellular pathways, such as NIMA-related kinase 7 (NEK7)/nucleotide-binding domain-like receptor protein 3 (NLRP3) and c-Jun N-terminal protein kinases (JNK)/stress activated protein kinases (SAPKs), as well as interleukin-6 (IL-6)/signal transducer and activator of transcription 3 (STATs), 8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] have been proven to closely account for BBR's polypharmacological effects. Furthermore, several direct proteomic targets of BBR, such as NEK7, UHRF1, RXRα, actin and ephrin-B2, 18,24,25,28,29 have been identified to explain its synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…24,30,31 The JNK pathway is mainly activated by various damage associated molecular patterns (DAMPs) including proinflammatory cytokines (tumor necrosis factor (TNF)-α and IL-1α), and the stimulation of JNK pathway gives rise to a marked increase of JNK phosphorylation (p-JNK) level, which lead to the progression of inflammatory, neurodegenerative and cell proliferative related diseases. 12,15,25,26 It is worth noting that BBR could suppress p-JNK to alleviate inflammation-related symptoms, such as obesity, insulin resistance, and exert effects on tumorous and neurodegenerative diseases. [32][33][34] However, the direct proteomic targets of BBR upon JNK signaling pathway are still unknown, so it is necessary to elucidate BBR's first target on JNK related diseases, so as to fully understand the multi-target pharmacological mechanism of BBR.…”
Section: Introductionmentioning
confidence: 99%